2014
DOI: 10.3233/jad-140702
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Dysfunctions in Middle-Aged Type 2 Diabetic Patients and Neuroimaging Correlations: A Cross-Sectional Study

Abstract: T2DM subjects presented cognitive dysfunctions compared with controls. Clinical-neuroimaging correlations corresponded to brain changes (reduced gray matter density and glucose metabolism) mainly in fronto-temporal areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
50
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 35 publications
8
50
0
Order By: Relevance
“…Impaired executive function and memory is correlated with reduced gray matter density and reduced glucose metabolism in the orbital and prefrontal cortex, temporal cortex (middle gyrus, parahippocampus, and uncus), and cerebellar regions [27]. While both T1DM [28] and T2DM [28] are associated with impaired cognition, the current data suggests a stronger association with T2DM.…”
Section: Clinical Effects Of Diabetes On Cognitionmentioning
confidence: 86%
“…Impaired executive function and memory is correlated with reduced gray matter density and reduced glucose metabolism in the orbital and prefrontal cortex, temporal cortex (middle gyrus, parahippocampus, and uncus), and cerebellar regions [27]. While both T1DM [28] and T2DM [28] are associated with impaired cognition, the current data suggests a stronger association with T2DM.…”
Section: Clinical Effects Of Diabetes On Cognitionmentioning
confidence: 86%
“…[32] Other studies of diabetes also found significant reductions in the GMV of the STG and MTG. [9,33] Another study showed that the GMV alterations in the MTG may predict mild cognitive impairment in type 2 diabetic patients. [34] Our findings in the STG and MTG may be associated with glucose dysregulation in prediabetes.…”
Section: Discussionmentioning
confidence: 99%
“…A longitudinal neuropsychological study has convincingly shown that patients with damage to PFC exhibit disorders in the higher cognitive functions (Cohen, 2000). Clinical research indicated that the terrible executive function and memory lesion in T2DM correlated predominantly with reduced glucose metabolism in the mPFC and orbital, temporal, and cerebellum regions (Garcia-Casares et al, 2014). Some studies suggested the memory dysfunction occurred in T2DM patients during acute hyperglycemia (Cox et al, 2005).…”
Section: Introductionmentioning
confidence: 99%